The Unwieldy Otherwise: Rethinking the Roots of Performance Studies in and through the Black Freedom Struggle - Hilton, Leon J.; Tallie, Mariahdessa Ekere (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
This project presents a syllabus that emerged out of an ongoing set of discussions between the two co-authors about how Black, Southern theatre and performance traditions—as well as embodied and transmitted genealogies of community engagement and activism—informed the intellectual, social, and political commitments that have suffused performance studies from its origins as an academic discipline. These discussions allowed us to generate a syllabus that provides the raw materials for an alternative and potentially radically destabilizing pedagogical approach to narrating the historical roots and development of performance studies over the past half-century. Specifically, we ask what shifts might occur in the performance studies classroom by narrating the field’s origins through the Free Southern Theatre, founded as a multiracial artistic ensemble in Jackson, Mississippi, in 1964. Our syllabus incorporates the key strands woven into the Free Southern Theatre’s aesthetic and political interventions, including Africanist cultural forms (such as the story circle); influences from the artistic and theatrical avant-garde; and populist theatre projects that developed in tandem with the revolutionary energies of the anti-imperialist, anti-colonial, and anti-capitalist struggles of the student movements of the 1960s. We ask how these largely hidden histories of resistance and dramaturgies of evasion reorient the way performance studies syllabi of the future tell the story of who and what matters, and in so doing materialize pedagogies of field formation that get frozen in place.